In vitro activity of ceftazidime/avibactam against carbapenem-nonsusceptible Klebsiella penumoniae isolates collected during the first wave of the SARS-CoV-2 pandemic: a Southern Italy, multicenter, surveillance study. (December 2022) - La Bella, Gianfranco; Lopizzo, Teresa; Lupo, Laura; Angarano, Rosa; Curci, Anna; Manti, Barbara; La Salandra, Giovanna; Mosca, Adriana; De Nittis, Rosella; Arena, Fabio
Highlights: During the first pandemic period, CAZ/AVI resistance remained infrequent in southern Italy. The presence of KPC-31 in a ST101 isolate was described for the first time. The spread of the high-risk epidemic ST147 NDM-1 producing clone was reported. Abstract: Objectives: Carbapenemase-producing Enterobacterales (CPE) represent a serious threat for human health being frequently resistant to most of available antibiotics classes. Recently, ceftazidime/avibactam (CAZ/AVI) has been approved for treatment of infections by Gram-negative bacteria, including class A CPE (including KPC-producing K. pneumoniae ). Following CAZ/AVI commercialization, resistance to this combination has been reported. The aim of this study was to evaluate the prevalence of CAZ/AVI resistance among carbapenem-resistant K. pneumoniae (CR-Kp) isolates recovered from bloodstream infections (BSI) and hospital-acquired pneumonia (HAP), representative of the contemporary southern Italy epidemiology, during the first pandemic wave of SARS-CoV-2. Methods: From Jan...20-Jun...20, 4 Laboratories, collected all consecutive, non-replicated CR-Kp from BSIs and HAPs. All isolates were subjected to i) MALDI-ToF identification; ii) antimicrobial susceptibility testing by microdilution method. CAZ/AVI resistant (CAZ/AVI-R) isolates were screened for presence of most common carbapenemase genes and subjected to whole genome sequencing for characterization. Results: A total of 89 isolates were collected. The majority of strains retained susceptibility to colistin, gentamicin and amikacin. Three strains (3/89, 3, 4%) were CAZ/AVI-R (MIC range 16/4-64/4 mg/L). Among CAZ/AVI-R, one was KPC-type producer (an ST101) while the remaining where NDM-type and VIM-type producers and belonged to ST147, and ST45, respectively. Conclusion: During the pandemic period, in southern Italy, CAZ/AVI resistance remained infrequent but high-risk Klebsiella pneumoniae epidemic clones, producing the KPC-31 variant and class B carbapenamases were reported from some of the included centers.